Hydrophobic–Hydrophilic Properties and Characterization of PIM-1 Films Treated by Elemental Fluorine in Liquid Perfluorodecalin - Belov N. A. Nikolay Alexandrovich; Alentjev (Alentiev) A. Yu. Aleksandr Yurjevich; Pashkevich D. S. Dmitry Stanislavovich; Voroshilov F. A. Fedor Anatolievich; Dvilis E. S. Edgar Sergeevich; Nikiforov R. Y. Roman; Chirkov S. V. Sergey; Syrtsova D. A. Daria; Kostina Ju. V. Julia; Asanov I. P. Igor; Bogdanova Yu. G. Yulia (2022, 2022)
Title screen